PENGARUH WISATA GUNUNG PANDAN DAN JUMLAH PENGUNJUNG TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT LOKAL : STUDI KASUS DI DESA SELAMAT KECAMATAN TENGGULUN KABUPATEN ACEH TAMIANG - KHILDA AMALIA (CV. Barokah Publsiher, 2025)
This research was conducted in Desa Selamat, Tenggulun District, Aceh Tamiang Regency to determine the influence of Gunung Pandan tourism and the number of visitors on the income of the local community. The study used a quantitative approach with a survey method through questionnaires distributed to 50 respondents running businesses around the tourist area. The data were analyzed using multiple linear regression with SPSS version 27. The results showed that partially, both Gunung Pandan tourism and the number of visitors significantly influenced community income, with significance values of 0.003 and 0.006, respectively. Simultaneously, both variables also had a significant influence with a significance value of 0.000 < 0.05. The coefficient of determination was 65.2%, indicating that tourism and the number of visitors contributed significantly to the increase in local community income around the Gunung Pandan tourist site.